Histological Structure of The Skin in The Thoracic and Abdominal Region of The Etawah Goats Cross Breed - Suwiti, Ni Ketut; Putri, Mergayanti Yudanta Eka; Suastika, Putu; Setiasih, Ni Luh Eka; Heryani, Luh Gde Sri Surya; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana; Vol. 11 No. 1 Pebruari 2019, 2019)
There have been studies of the histological structure of male and female goat skins. The histological structure and histomorphometry were taken from two region of skin, which is the thorax and abdomen. The Samples were collected from 2-3 years old Etawah goat, and than was stained using a HarrisHematoxilin Eosin method. The data were analysis based on the region and sex.  The results showed that the histological structure of Etawah cross breed consists of three layers were epidermis, dermis, and hipodermis respectively. The epidermis composed by stratum corneum, granulosum, spinosum, and basal. We were found keratin layer on the surface of epidermis. The dermis consists of papillare and reticulare stratum. That was found many sebaceous glands, sudorifera gland, pili muscle, hair follicles, blood vessels, and collagen fibers. The hypodermis layers of Etawah cross breed females skin mostly consists of the fatty tissue, whereas in males we have found thick and horizontally arranged connective tissue. The skin layer on male Etawah cross breed, thorax region thicker than the abdomen. The region and sex may have an effect on the histology structure and histomorphometry of Etawah cross breed skin.